2005
DOI: 10.1097/01.ico..0000138832.3486.70
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Fungal Keratitis and Endophthalmitis Following Penetrating Keratoplasty

Abstract: The overall incidence of fungal infection following penetrating keratoplasty is low, but all cases in our study were associated with positive rim cultures. Whether prophylactic antifungal therapy would be of any benefit in the presence of a positive corneoscleral rim culture has not yet been determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 23 publications
6
76
0
1
Order By: Relevance
“…Another short series suggested a possible link between post-keratoplasty endophthalmitis and donor malignancy. 19 This was confirmed by a study by the Eye Bank Association of America, 20 which reported that hospitalization or cancer at the time of Abbreviations: DA, donor age (years); DTT, death-to-tissue retrieval time (hours); TRT, tissue retrieval-to-reception time (hours). It represents the likelihood for a given cornea to be suitable for transplantation according to donor age, death-to-tissue retrieval time, and tissue retrievalto-reception time.…”
Section: Discussionsupporting
confidence: 55%
“…Another short series suggested a possible link between post-keratoplasty endophthalmitis and donor malignancy. 19 This was confirmed by a study by the Eye Bank Association of America, 20 which reported that hospitalization or cancer at the time of Abbreviations: DA, donor age (years); DTT, death-to-tissue retrieval time (hours); TRT, tissue retrieval-to-reception time (hours). It represents the likelihood for a given cornea to be suitable for transplantation according to donor age, death-to-tissue retrieval time, and tissue retrievalto-reception time.…”
Section: Discussionsupporting
confidence: 55%
“…However, it remains a major concern in corneal transplantation. [15][16][17][18][19][20] In the current study, postoperative bullous keratoplasty (9/14, 64.3%) was the major risk factor for keratitis due to ocular surface diseases with recurrent erosion of the epithelium. 21,22 Fusarium infection is the most common pathogen leading to cornea perforation (28.8%), followed by P. aeruginosa keratitis (21.4%).…”
Section: Resultsmentioning
confidence: 99%
“…Fungal infection following penetrating keratoplasty has a reported incidence rate of 0.16% [1,2]. The recent increase in Descemet's stripping automated endothelial keratoplasty (DSAEK) has been accompanied by an increase in postoperative fungal infection, and five cases have been reported [3][4][5][6].…”
Section: Introductionmentioning
confidence: 98%